2021
DOI: 10.1186/s12711-021-00689-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a regulatory mutation upstream of the BMP2 gene associated with carcass length in pigs

Abstract: Background Carcass length is very important for body size and meat production for swine, thus understanding the genetic mechanisms that underly this trait is of great significance in genetic improvement programs for pigs. Although many quantitative trait loci (QTL) have been detected in pigs, very few have been fine-mapped to the level of the causal mutations. The aim of this study was to identify potential causal single nucleotide polymorphisms (SNPs) for carcass length by integrating a genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 69 publications
0
27
0
2
Order By: Relevance
“…In the case of the CRCL peak (SSC17, Fig. 3 D), BMP2 (bone morphogenetic protein 2) was suggested as a strong candidate in previous studies conducted on these crosses [ 7 , 22 ] but also in other pig populations (Duroc × (Landrace × Yorkshire), [ 42 ]). In the latter study, the authors indicated that a SNP (rs320706814) was the main cause of the effect on carcass length.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the case of the CRCL peak (SSC17, Fig. 3 D), BMP2 (bone morphogenetic protein 2) was suggested as a strong candidate in previous studies conducted on these crosses [ 7 , 22 ] but also in other pig populations (Duroc × (Landrace × Yorkshire), [ 42 ]). In the latter study, the authors indicated that a SNP (rs320706814) was the main cause of the effect on carcass length.…”
Section: Discussionmentioning
confidence: 89%
“…However, we could not confirm the SNP effect in our population, as this SNP was not significantly associated nor in LD with the significant SNPs, small indels, SVs, or TRs we have identified. Li et al [ 42 ] did not exclude the option that the causative mutation could be in fact a non-SNP or non-small indel variant. Therefore, coupled with our findings, it could be hypothesized that the nearby TR-enriched lncRNAs (upstream: ENSSSCG00000043546 , ENSSSCG00000047884 ; downstream: ENSSSCG00000044805 ) could drive the molecular mechanisms involving the BMP2 in carcass length variation in the current F 2 crosses.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that some SNP sites had been deleted because the labeling density and conditions were too strict. Subsequently, new SNPs on IMF can be selected by increasing the labeling density or selecting a looser quality control condition [ 43 ]. Although only three SNPs were screened on 12 hIMF, both SSC2 (H3GA0054148) and SSC15 (WU_10.2_15_140224592) reached a loose genome-wide significant threshold (1/28066).…”
Section: Resultsmentioning
confidence: 99%
“…Haplotype block analysis was carried out using PLINK v1.90 [ 28 ] and Haploview [ 41 ] software. According Gebriel et al [ 42 ], the search for genes was within the SNP locus and 500 Kb upstream and downstream of the GWAS-significant SNP [ 43 ] on Sscrofa11.1 in the Ensembl database ( accessed on 13 October 2022). Gene function annotation was performed on the screened genes, and KOBAS 3.0 [ 44 ] was used to further perform gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis on all of the screened genes.…”
Section: Methodsmentioning
confidence: 99%
“…Remarkably, this variant explained 13.65% of the total phenotypic variance and the homozygous C/C animals were on average 4.01 cm longer than the T/T homozygotes (Figure 4b,c). BMP2 has been repeatedly shown to be associated with growth traits in pigs and a recent study implicated a regulatory variant upstream of the BMP2 gene and validated its functional impact using reporter genes (Li et al, 2021a). This regulatory variant was the third most significant SNP under this peak in our analysis.…”
Section: Resultsmentioning
confidence: 99%